PENGARUH E-WOM, PROMOSI, DAN BRAND LOVE TERHADAP KEPUTUSAN PEMBELIAN SKINCARE THE ORIGINOTE - Fauziah Aryanti, Mega; Astini, Rina (Creative Research Management Journal, 2025)
This study aims to analyze the influence of Electronic Word of Mouth (E-WOM), promotion, and brand love on the purchase decision of The Originote skincare products. The research employed a quantitative method using a survey of 105 respondents who had previously used the products. Data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS. The results indicate that E-WOM and brand love have a positive and significant effect on purchase decisions, while promotion has a positive but not significant effect. The adjusted R² value of 66.1% suggests that the independent variables substantially explain the dependent variable. This study is limited to users of The Originote products, so the findings may not be generalized to other brands or product categories. The contribution of this research lies in enriching the literature on digital marketing and brand loyalty, as well as providing practical implications for skincare industry players in designing more effective brand communication strategies.